Environmental Campaign Advocate through Waste Digital Bank at Rural Area in Bali, Indonesia - Dewi, Wayan Weda Asmara; Sarwono , Billy K.; Pasandaran, Camelia Catharina (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2024)
Discussions about environmental issues, one that has become quite the topic of conversation this decade is related to global warming, for example related to waste. Garbage has a significant contribution to environmental damage. The issue of global warming is an emerging and growing issue. The purpose of the research is to understand the proprietary strategy of Griya Luhu's in delivering environmental campaign digital waste banks at Rural Area. Environmental communication is one of the advocacy efforts. Environmental campaign advocacy is the act of persuading or arguing in favor of a particular cause, policy, idea or set of values on an issue. Advocacy is a powerful medium for various social and environmental change organizations. Existing environmental campaign advocacy all this time only focuses on urban areas. Economic limitations and waste issues become the main reason why Griya Luhu, an NGO Bali-Indonesia based, wants to give environmental campaigns to rural communities on Bali island through their program called Digital Bank Sampah (Waste Digital Bank). This research is done with an in-depth interview with the Chairman dan members of Griya Luhu. The outcome of this research shows that Griya Luhu uses various strategies, including a communal approach, raising environmental issues, and empowering the community during the program Waste Digital Bank. Griya Luhu's primary strategy is empowering the community, especially in rural areas. The form of their empowerment is to push the people to be able to use digital technology and want to make waste bank work more transparent. Thus the community is more concerned with the environment, especially the problem of waste